Massive haemoptysis caused by a long‐standing foreign body in the airway. Issue 7 (3rd September 2020) - Nagano, Hiroaki; Maeda, Akiko; Kato, Takashi; Kitamura, Ryoichi; Higashiura, Wataru
Abstract: The presence of foreign bodies (FB) in the airway is a potentially life‐threatening event. We encountered a rare case of long‐standing bronchial FB complicating with intermittent massive haemoptysis in a 42‐year‐old man. He denied any prior history of aspiration. The FB was buried deep in the bronchial epithelium and could not be removed using bronchoscopy. Bronchial angiography revealed marked dilation of the inferior lobe branch of the bronchial artery due to the FB. Bronchial artery embolization (BAE) was performed, which was followed by left lower lobectomy (LLL). The FB was keyhole‐shaped, composed of a plastic‐like material, with an appearance akin to an ancient Japanese burial mound. This case was extremely unique, since a strange FB remained in the bronchi for a long time, which caused massive haemoptysis due to the dilation of the bronchial artery. Abstract : This case was a very unique in that a strange foreign body in the bronchi remained for a long time and massive haemoptysis was caused by dilation of the bronchial artery.